ANALISIS KUALITAS LAYANAN JARINGAN INTERNET PADA INSTITUT INFORMATIKA DAN BISNIS DARMAJAYA - Sudibyo, Novi Herawadi (Prosiding Seminar Nasional Darmajaya, 2017)
Internet users now include all the people, from rural to urban, from small children up to parents with different needs. In the world of education moreover the role of the internet is needed to support the learning process, teaching and business processes. Institute Informatics and Business Darmajaya is a college that all activities are assisted by the internet, including internet facilities are also given to students. With all activities that already use the internet of course to support the process the quality of network services must be in good performance. Network service quality analysis is a process to know the quality of network services that have been given, in this study the standardization used to determine the quality of services using TIPHON standardization with delay parameters, jitter, packet loss, and Thoughput. In search of data process done by doing measurement at hotspot / wifi in IIB Darmajaya environment and do measurement by using nettoolsaxcent tools in searching data.Keywords: IIB Darmajaya, Internet, Quality of service